1995
DOI: 10.1152/ajpendo.1995.268.6.e1108
|View full text |Cite
|
Sign up to set email alerts
|

1,25(OH)2D3 suppresses expression and secretion of atrial natriuretic peptide from cardiac myocytes

Abstract: We have examined the effects of 1,25-dihydroxyvitamin D3 [1,25(OH)2D3] on the expression of the rat atrial natriuretic peptide (ANP) gene and the secretion of the encoded protein product in neonatal rat cardiac myocyte cultures. 1,25(OH)2D3 effected a dose- and time-dependent inhibition of agonist-stimulated ANP secretion, which was accompanied by a reduction in the levels of the ANP mRNA transcript. The latter effect appeared to derive, at least in part, from suppression of ANP gene transcription. Of interest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
1
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 24 publications
2
37
1
1
Order By: Relevance
“…Finally, our previous demonstration that VD suppresses expression and secretion of ANP (12,13,43) seems, at first glance, to be physiologically inconsistent with the data presented here, because a reduction in ligand levels would be predicted to offset the increase in receptor activity. However, it is important to point out that the VD-dependent inhibition of ANP expression is largely confined to hypertrophy-dependent expression (e.g., that induced by endothelin treatment) and reflects a global antagonism of the hypertrophic process rather than isolated inhibition of the ANP gene.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…Finally, our previous demonstration that VD suppresses expression and secretion of ANP (12,13,43) seems, at first glance, to be physiologically inconsistent with the data presented here, because a reduction in ligand levels would be predicted to offset the increase in receptor activity. However, it is important to point out that the VD-dependent inhibition of ANP expression is largely confined to hypertrophy-dependent expression (e.g., that induced by endothelin treatment) and reflects a global antagonism of the hypertrophic process rather than isolated inhibition of the ANP gene.…”
Section: Discussioncontrasting
confidence: 89%
“…Subsequent studies from the same group indicated that a major component of the hypertrophy seen in vitamin D-deficient animals reflects expansion of the interstitial compartment in the heart (predominantly cardiac fibroblasts) with increased production of extracellular matrix proteins (11). VD has been shown to reduce endothelin-stimulated ANP and BNP gene expression (markers of myocyte hypertrophy) and transcription in cultured neonatal rat atrial (12) and ventricular (13) myocytes and to suppress the hypertrophic response to endothelin, a well known hypertrophic agonist in the cultured ventricular myocyte model (13). It is interesting that this suppressive activity seems to require structural features of the VDR that are more typically associated with the activation function of this receptor (14,15).…”
mentioning
confidence: 99%
“…In previously published studies (36,37), both RXR and vitamin D receptor ligands were shown to suppress basal and endothelin-1-activated expression of the ANF gene in rat atrial myocytes. In addition, retinoid or vitamin D ligands were shown to inhibit ET-1-induced cardiomyocyte hypertrophy (15).…”
Section: Discussionmentioning
confidence: 87%
“…After previous observations suggesting an involvement of 1,25(OH)2D in the regulation of atrial natriuretic peptides (ANPs) [25], Li and Gardner showed that the liganded VDR suppressed ANP transcription by binding to the promoter region of this gene [26]. Further studies confirmed that 1,25(OH)2D inhibits the secretion of natriuretic peptides in atrial and ventricular myocytes [13,27]. It was demonstrated that the inhibition of the ANP promoter activity requires the DNA-binding and the ligandbinding domain of the VDR [28].…”
Section: Vitamin D Effects On Gene Expression Of Natriuretic Peptidesmentioning
confidence: 79%